Displacement in Architecture An analytical study in contemporary mosques design - Alâ€SalhiParizat Qassim; Alâ€NouaimiNada khteer; Al-Qaraghuli, Anwar Subhi Ramdan (Iraqi Journal of Architecture and Planning, 2009)
Previous architectural studies have presented new concems for contemporary design of mosques. These concems were raised on both academic and professional levels. what is significant is to elaborate on special aspects of these concems, instead of limited understanding without it being comprehensive enough to utilizc the mental and intellectual content in the local meliue. Displacement represents a major concern specially its relationship to concepts and forms; and what the design process aims at to achieve uniqueness in expression. It is possible to enterprite unique qualities in ideas expressed architecturally as a displacement of current types, which is founded on a deep design problem. This paper discusses displacement with the abore rtat"d context, aiming to achieve. a contemporary frame work theory a discussion of current theories Ind application to achieve a distinguish mosque aichitecture.